Proceeding Report of the 40th Anniversary of National Meteorological Agency, Official endorsement of the National Framework for Climate Services an International Scientific Conference - Getachew, Abate; Teshome, Asaminew; Teshome, Fetene; Hailemariam, Kinfe; Bekele, Leta; Abera, Mulualem; Fekadu, Kassa; Radeny, Maren A.O.; Demissie, Teferi Dejene; Makonnen, Brook T.; Solomon, Dawit (National Meteorology Agency, 2021)
Ethiopia is located in the Horn of Africa within 3–15° N and 33–48° E, bordered by Eritrea to the north and northeast, Djibouti to the east, Sudan to the west, Kenya to the south, and Somalia to the south and east. It covers an area of about 1.14 million square kilometers. The country's topography consists of high and rugged plateaus and peripheral lowlands. Elevations in the country range from 160 meters below sea level (northern exit of the Rift Valley) to over 4600 meters above sea level (of northern mountainous regions). The highest mountains are concentrated on the northern and southern plateaus of the country. A large percentage of the country consists of high plateaus and mountain ranges, dissected by major rivers such as Blue Nile, Tekeze, Awash, Omo, Wabi Shebelle, etc. Overall, Ethiopia consists of 9 major rivers and 19 lakes. The Blue Nile, the chief headstream of the Nile, rises in Lake Tana in northwest Ethiopia. The meteorological observation started in the 1890s with few meteorological stations. In 1951, meteorological services were established as a small unit in the then Civil Aviation Department to render aeronautical services. Since then, meteorological observation has been expanding over Ethiopia. As the importance of meteorology was realized by other economic sectors, National Meteorological Services Agency (NMSA) was established by the Government Proclamation Number 201/1980. Besides, NMA started seasonal forecasting and advisory service in 1987 for three seasons, namely Belg (February - May), Kiremt (June-September), and Bega (October-January). The primary duty of NMA is to support all country's socio-economic developments by delivering climate services. Moreover, NMA has more than one thousand three hundred conventional Meteorological stations, three hundred automatic weather stations, five AWOS, three air pollution monitoring stations, three upper air stations, one radar, and eleven satellite receiver stations. The government of Ethiopia is determined to eradicate poverty and become a prosperous country by 2030. In this regard, addressing climate variability and change play a pivotal role in achieving this goal. To this effect, NMA is equipping with modern weather observing and monitoring capabilities and improving processing, analyzing, interpreting, and forecasting weather and climate capabilities at a high resolution and accuracy to meet the end-user's demands and effectively support all socio-economic developments of the country. NMA collaborates with all key stakeholders and partners through continuous engagement on climate services. The NFCS, endorsed during the NMA 40th Anniversary, is envisaged to strengthen collaborative co-production between climate services provider (NMA) and climate service beneficiaries institutions (MoWIE, EFCCC, MoA, MoH, and NDRMC). To commemorate its 40th anniversary, NMA has organized a conference with a theme of "Forty Years of Climate and Weather Services in Ethiopia" on May 25-26, 2021, at Skylight Hotel, Addis Ababa, Ethiopia. Generally, three main sessions were held during the conference. These include; Session one: panel discussion and opening ceremony; session two: presentations on the history of NMA and NFCS Ethiopia, official endorsement of NFSC Ethiopia, and certificate wards; and session three: parallel session of four groups and paper presentations on different thematic areas were made. The 40th anniversary was attended by ministers, commissioners, heads of organizations, and representatives from the WMO Africa regional office, international institutes representatives, experts from different organizations, lecturers, researchers, and NMA officials and staff. This document is proceedings of the 40th anniversary, including summaries of the opening session and the presentations.